Understanding the moderator role on covid-19 pandemic anxiety on the relationship between internet addiction and online shopping addiction - AYSUNA TÜRKYILMAZ, CEYDA (My University, 2022)
Internet addiction is one of the most important drivers of online shopping addiction. During Covid-19 pandemic people had to spend more time in their homes and had to use internet more than before to do their tasks. One of the tasks that should be performed on internet is shopping. On the other hand, it’s obvious that Covid-19 pandemic has negative outcomes in terms of economy and psychology. One of the negative outcomes of pandemic is anxiety. In this study, the moderator role of Covid-19 anxiety on the relationship between internet addiction and online shopping addiction is examined. Although several studies are conducted during pandemic about the effects of pandemic this topic is not investigated. In this regard, this study is unique and suppose to add value to the related literature. The results of the analysis show that online shopping addiction consisted of three factors. Among those factors, the moderator role of Covid-19 anxiety was supported only for the negative effect factor. In other words, Covid-19 anxiety has moderating effect on the relationship between internet addiction and negative effect dimension of online shopping addiction. Finally, some suggestions were provided for the online shopping firms depending on the findings of the study.

İnternet bağımlılığı çevrimiçi alışveriş bağımlılığının önemli nedenleri arasındadır. Covid-19 pandemisinde evlerinde daha fazla zaman geçirmek durumunda kalan bireyler daha fazla internet kullanmak ve işlerinin çoğunu çevrimiçi olarak yapmak zorunda kalmışlardır. Bu işlerden biri de alışveriştir. Öte yandan, Covid-19 pandemisinin insanlar üzerinde gerek ekonomik gerekse psikolojik olumsuz etkileri bilinmektedir. Bu etkilerden biri anksiyetedir. Bu çalışmada, internet bağımlılığının online alışveriş bağımlılığı üzerindeki etkisinde Covid-19 pandemisinin yarattığı anksiyetenin düzenleyici etkisi incelenmiştir. Pandemi zamanında pandeminin etkilerinin araştırıldığı çalışmaların oldukça fazla olmasına rağmen, bu konunun araştırılmamış olması çalışmanın özgün yönünü oluşturmaktadır. Çevrimiçi anket yöntemiyle 304 kişiden toplanan verilerin analizi sonucunda çevrimiçi alışveriş bağımlılığı üç faktör altında toplanmıştır. Analiz sonuçlarına göre Covid-19 pandemisinin yarattığı anksiyetenin, internet bağımlılığının çevrimiçi alışveriş bağımlılığı boyutlarından olumsuz etki üzerinde düzenleyici rolü olduğu sonucuna ulaşılmıştır. Çalışmanın son kısmında ise, çevrimiçi satış yapan işletmelere öneriler sunulmuştur
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Pazarlama; Social Sciences and Humanities; Management; Marketing; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; Online Shopping Addiction; Internet Addiction; Covid-19; Pandemic; Covid-19 Pandemic Anxiety; Çevrimiçi Alışveriş Bağımlılığı; İnternet Bağımlılığı; Pandemi; Anksiyete; Covid-19 Pandemi Anksiyetesi